CT Evaluation of Anatomical Variations in Osteomeatal Complex in Patients with Deviated Nasal Septum (Bangladesh Journal of Otorhinolaryngology, 2016)
Background:The presence of septal deviation has been positively associated with sinus disease, especially osteomeatal complex disease and anterior and posterior ethmoid disease.Computerized tomographic imaging (CT) of the paranasal sinuses has become a widely accepted tool for assessing the paranasal sinuses (PNS) and providing a detailed anatomy of the lateral nasal wall.Objective:The objective of the study was to identify the anatomical variations of lateral nasal wall and paranasal sinuses in patients with Deviated nasal septum.Methods:Computerized tomographic (CT) examination was carried out using the bone algorithm in the coronal plane in 40 patients who met the inclusion criteriain the Postgraduate Department of Otorhinolaryngology and Head and Neck Surgery, SMHS Hospital an associated Hospital of Government Medical College, Srinagar from March 2011 to May 2012.Results:In our study, CT Nose and PNS revealed Deviated nasal septum in 40 (100%) patients, Hypertrophied Inferior turbinate in 11 (27.50%) patients, Concha bullosa in 5 (12.50%) patients, Paradoxical Middle turbinate in 8 (20%) patients, Everted Hypertrophied Uncinate in 2 (5%) patients, Aggernasi cells in 4 (10%) patients, Haller cells in 3 (7.50%) patients and Onodi cells in 2 (5%) patients.Conclusion:The most common anatomical variation associated with deviated nasal septum was Hypertrophied Inferior turbinate and the least encountered variation was Everted Hypertrophied Uncinate and Onodi cells. The CT scan provides supplementary clinical data to the history and endoscopic examination and assists in directing surgical treatment to the affected areas.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 90-93